Improvement of Marketing Management in the Enterprise of Industrial Products - Musayeva Shaira Azimovna; Usmanov Farzod Shokhrukhovich; Muminova Farangiz Alamovna (Journal of Artificial Intelligence and Digital Economy, 2024)
In this article, we will increase the volume of production by purchasing innovative equipment, increasing new workplaces and increasing the number of collections offered, bringing joy to people's lives, creating comfort and convenience by providing a wide selection of high-quality carpet products. reviewed.